KOMUNIKASI KELOMPOK PADA 234 SOLIDARITY COMMUNTIY PEKANBARU DALAM MEMBANGUN KOHESIVITAS - M. Arifuddin "; Tantri Puspita Yazid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
wide variety of community exists in Indonesia, one of which is a community of 234 Solidarity Community or shortened by 234 SC. Community 234 SC is already scattered in various regions in Indonesia and to foreign countries such as Malaysia, Beijing, and the Netherlands. Community of 234 SC is also entered in Riau, one of them is in Pekanbaru city and called 234 SC Pekanbaru. 234 SC Pekanbaru interaction and communication to improve the existence, solidarity among the members, as well as the cohesiveness in the group. This study aims to determine patterns of communication and the factors that influence the effectiveness of communication 234 SC Pekanbaru communities in building cohesiveness. This study uses qualitative descriptive method, with the selection of informants using purposive, which selects five selected informants, namely a community chief, two officers and two members of the community 234 SC Pekanbaru. Data collection techniques using observation, interviews, and documentation. For the data analysis, refer to the interactive model of Miles and Huberman. For checking the validity of the data using the extension of participation and triangulation techniques. The results of this study indicate that the community 234 SC Pekanbaru to communicate face-to -face and virtual communication in which communication and interaction that occurs can be with anyone, anytime and anywhere, communication is bi-directional, and communication networks that are formed in the form of schemes all channels. In this community interacts using symbols in the form of everyday language commonly used by the people. Cooperation in the community is more dominant than the competition, this community has a code of ethics written which is used as the norms and rules, this community always choose and create an atmosphere that fits in activities in order to create a sense of comfort and conducive, there are no rules in the selection of seating positions, joke or humor is allowed to use in order to become familiar atmosphere and not stuffy. Of communication patterns and the factors that influence the effectiveness of this form of communication that makes a community cohesiveness 234 SC Pekanbaru be solid and sustain each other. Keywords: Communications group , Community 234 SC , Cohesiveness